2020
DOI: 10.1111/jvim.15978
|View full text |Cite
|
Sign up to set email alerts
|

Changes in systolic blood pressure in dogs with pituitary dependent hyperadrenocorticism during the first year of trilostane treatment

Abstract: Background: Systemic hypertension (SH) is common in dogs and humans with hypercortisolism and can persist after treatment. Objectives: To evaluate changes in prevalence of SH and systolic blood pressure (SBP) in dogs with pituitary-dependent hyperadrenocorticism (PDH) during the first year of trilostane treatment, its relationship with disease control and selected laboratory variables, and their response to antihypertensive treatment. Animals: Fifty-one dogs with PDH treated with trilostane Q12h. Methods: Pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 67 publications
(346 reference statements)
3
7
1
Order By: Relevance
“…However, the low median final trilostane dose, considering that monitoring was based on clinical signs, and the long median survival time achieved can be interpreted as a good clinical control as previously described by other authors using this treatment protocol 12 . Moreover, in a previous study of the same research group involving 51 of the dogs included in the present one, all dogs included shown a good clinical control of the disease at some point during the first year of treatment 19 …”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…However, the low median final trilostane dose, considering that monitoring was based on clinical signs, and the long median survival time achieved can be interpreted as a good clinical control as previously described by other authors using this treatment protocol 12 . Moreover, in a previous study of the same research group involving 51 of the dogs included in the present one, all dogs included shown a good clinical control of the disease at some point during the first year of treatment 19 …”
Section: Discussionsupporting
confidence: 66%
“…12 Moreover, in a previous study of the same research group involving 51 of the dogs included in the present one, all dogs included shown a good clinical control of the disease at some point during the first year of treatment. 19 In conclusion, low dose twice daily trilostane treatment provides a slightly longer survival time than previously reported in dogs with CS treated with once or twice daily higher trilostane doses. Older age, calcinosis cutis, a thin BCS (i.e.…”
Section: F I G U R Ementioning
confidence: 56%
See 2 more Smart Citations
“…It is well documented that systemic hypertension (SH) is a common complication of CS, which may be present in approximately 70-85% of people [3][4][5][6] and 31-86% of dogs at the time of diagnosis [7][8][9][10][11][12][13][14][15]. There are also some factors that have been associated with SH in dogs with CS, such as lower potassium concentrations, thrombocytosis, higher cortisol concentrations, or higher urinary protein to creatinine ratio [7,[10][11][12][13]15].…”
Section: Introductionmentioning
confidence: 99%